2010
DOI: 10.1111/j.1469-0691.2009.02879.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher rates of streptococcal colonization among children in the Pacific Rim Region correlates with higher rates of group A streptococcal disease and sequelae

Abstract: Group A streptococcal (GAS) pharyngeal colonization rates were determined among 1061 asymptomatic students in Hawaii and American Samoa where acute rheumatic fever rates are high. All GAS isolates were emm sequence typed. Although pharyngeal colonization rates were low in Hawaii (3.4%), Pacific Islander children had significantly higher colonization rates (5.7% versus 1.2% in other ethnic groups, p<0.05). The colonization rate was higher in American Samoa (13%). Few emm types that were infrequently observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Streptococcus pyogenes (group A streptococcus [GAS]) is an important primary pathogen causing severe infections like necrotizing fasciitis and toxic shock syndrome, but it also colonizes mucosal surfaces, often asymptomatically. Mucosal carriage of GAS in the throat (13), gastrointestinal tract (4), and rectovaginal tract (5, 6) can serve as principal reservoirs for community infections. Although the rate of transmission from carriers is lower than in acutely infected individuals, this reservoir is important on a population level, as rates of carriage greatly eclipse rates of acute infections in the community (7).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pyogenes (group A streptococcus [GAS]) is an important primary pathogen causing severe infections like necrotizing fasciitis and toxic shock syndrome, but it also colonizes mucosal surfaces, often asymptomatically. Mucosal carriage of GAS in the throat (13), gastrointestinal tract (4), and rectovaginal tract (5, 6) can serve as principal reservoirs for community infections. Although the rate of transmission from carriers is lower than in acutely infected individuals, this reservoir is important on a population level, as rates of carriage greatly eclipse rates of acute infections in the community (7).…”
Section: Introductionmentioning
confidence: 99%
“…The erythromycin resistance rate (ϳ3%) has been low among group A streptococcus (GAS) isolates in Hawaii, where impetigo, acute rheumatic fever, and clusters of necrotizing fasciitis have been reported (5)(6)(7)(8)(9)(10); G. Erdem, G. Matsuura, G. Wheelen, C. Mizumoto, D. Esaki, and P. V. Effler, presented at the XVIIth Lancefield International Symposium on Streptococci and Streptococcal Diseases, Porto Heli, Greece, 2008). During a retrospective survey of 250 GAS cultures collected from patients with invasive GAS disease identified between the years 2005 and 2007, the reviews of the clinical information incidentally showed erythromycin and clindamycin resistance in five patients.…”
mentioning
confidence: 99%
“…Several articles refer to a high RF incidence in native Hawaiians; however, no rates current after 1988 were found . It appears that little Government emphasis is placed on the illness…”
Section: Resultsmentioning
confidence: 99%